2012
DOI: 10.1017/thg.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

The Young Netherlands Twin Register (YNTR): Longitudinal Twin and Family Studies in Over 70,000 Children

Abstract: The Netherlands Twin Register (NTR) began in 1987 with data collection in twins and their families, including families with newborn twins and triplets. Twenty-five years later, the NTR has collected at least one survey for 70,784 children, born after 1985. For the majority of twins, longitudinal data collection has been done by age-specific surveys. Shortly after giving birth, mothers receive a first survey with items on pregnancy and birth. At age 2, a survey on growth and achievement of milestones is sent. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 73 publications
0
159
0
Order By: Relevance
“…In all five samples, the DZ correlation for intelligence exceeded half the MZ correlation, so an ACE model was fit. In two of the samples, Australia and the US, this was also the case for personality, but in the other three the DZ correlation for personality was less than half the MZ correlation, suggesting the presence of non-additive genetic variance, modeled as Dominance in an ADE model (e.g., van den Berg et al, 2014).…”
Section: Analysesmentioning
confidence: 82%
“…In all five samples, the DZ correlation for intelligence exceeded half the MZ correlation, so an ACE model was fit. In two of the samples, Australia and the US, this was also the case for personality, but in the other three the DZ correlation for personality was less than half the MZ correlation, suggesting the presence of non-additive genetic variance, modeled as Dominance in an ADE model (e.g., van den Berg et al, 2014).…”
Section: Analysesmentioning
confidence: 82%
“…18,19 The NTR is a population-based register of Dutch twins recruited at birth and measured longitudinally at ages 1 through 18. The sample consisted of 1316 individuals from 662 families (978 twins, 231 siblings, and 107 of their parents).…”
Section: Materials and Methods Samplementioning
confidence: 99%
“…15,17 The 43 genes considered in the present study are a subset of the genes identified in a recent study that used homozygosity mapping, exon enrichment, and next-generation sequencing in consanguineous families with autosomal-recessive intellectual disabilities to identify single, presumably disease-causing variants in 50 novel candidate genes. 11 The genome-wide data set of the Netherlands Twin Register (NTR), 18 used in the present study, contains SNP data on 43 of these 50 genes (Table 1), including 1227 genotyped SNPs in total (Supplementary Table S1). …”
Section: Introductionmentioning
confidence: 99%
“…Venous blood samples were drawn in the morning after an overnight fast, and multiple ethylenediaminetetraacetic acid (EDTA) tubes were collected for isolation of DNA and RNA and assessment of hematological profiles. Phenotyping through longitudinal surveys and blood sampling procedures have been described in detail previously (Boomsma et al, 2006;van Beijsterveldt et al, 2013;Willemsen et al, 2010Willemsen et al, , 2013.…”
Section: Subjects and Samplesmentioning
confidence: 99%